Hypertension Subtypes, Mortality Risk, and Differential Effects Between Two Hypertension Guidelines - Mai, Hui; Li, Chao; Chen, Kangyu; Wu, Zhenqiang; Liang, Xuanyi; Wang, Yongjuan; Chen, Tao; Chen, Fengjian (Frontiers in Medicine, 2022)
Aim: To examine which hypertension subtypes are primarily responsible for the difference in the hypertension prevalence and treatment recommendations, and to assess their mortality risk if 2017 American College of Cardiology (ACC)/American Heart Association (AHA) hypertension guideline were adopted among Chinese adults. Methods We used the nationally representative data of China Health and Retirement Longitudinal Study (CHARLS) to estimate the differences in the prevalence of isolated systolic hypertension (ISH), systolic diastolic hypertension (SDH) and isolated diastolic hypertension (IDH) between the 2017 ACC/AHA and the 2018 China Hypertension League (CHL) guidelines. We further assessed their mortality risk using follow-up data from the China Health and Nutrition Survey (CHNS) by the Cox model. Results The increase from the 2017 ACC/AHA guideline on hypertension prevalence was mostly from SDH (8.64% by CHL to 25.59% by ACC/AHA), followed by IDH (2.42 to 6.93%). However, the difference was minuscule in the proportion of people recommended for antihypertensive treatment among people with IDH (2.42 to 3.34%) or ISH (12.00 to 12.73%). Among 22,184 participants with a median follow-up of 6.14 years from CHNS, attenuated but significant associations were observed between all-cause mortality and SDH (hazard ratio 1.56; 95% CI: 1.36,1.79) and ISH (1.29; 1.03,1.61) by ACC/AHA but null association for IDH (1.15; 0.98,1.35). Conclusion Adoption of the 2017 ACC/AHA may be applicable to improve the unacceptable hypertension control rate among Chinese adults but with cautions for the drug therapy among millions of subjects with IDH.